2009
DOI: 10.1007/s11458-009-0034-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of MCM-41 supported amino-palladium complex and its catalytic performance for heck reaction

Abstract: Using MCM-41 as the supporter, a series of MCM-41 supported amino-palladium complexes has been prepared and characterized by XRD (X-ray diffraction) and XPS (X-ray photoelectron spectroscopy), etc. The XRD and XPS results indicate that the Pd coordinates with the -NH 2 groups on the MCM-41 surface, and the structure of MCM-41 has been not damaged. Its catalytic performance for Heck arylation of alkene with aryl iodide shows that the catalysts have high activity and stereoselectivity in 70-90°C. The product of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
2
0
0
Order By: Relevance
“…Similar chemical shifts to those of Pd3 were found for very small palladium nanoparticles on alumina [53] and iron oxide, [54] for [Pd(NH 3 ) 4 Cl 2 ] nanowires, [55] nitrogen-containing conjugated polymer-palladium systems, [56] and an amino-functionalized MCM-41-supported Pd2 complex [57] and are attributed to Pd 2 + bound to different ligands (Cl, N, O). Similar chemical shifts to those of Pd3 were found for very small palladium nanoparticles on alumina [53] and iron oxide, [54] for [Pd(NH 3 ) 4 Cl 2 ] nanowires, [55] nitrogen-containing conjugated polymer-palladium systems, [56] and an amino-functionalized MCM-41-supported Pd2 complex [57] and are attributed to Pd 2 + bound to different ligands (Cl, N, O).…”
Section: Nature Of the Pd Species On Ncnts Determined By Xpssupporting
confidence: 59%
See 1 more Smart Citation
“…Similar chemical shifts to those of Pd3 were found for very small palladium nanoparticles on alumina [53] and iron oxide, [54] for [Pd(NH 3 ) 4 Cl 2 ] nanowires, [55] nitrogen-containing conjugated polymer-palladium systems, [56] and an amino-functionalized MCM-41-supported Pd2 complex [57] and are attributed to Pd 2 + bound to different ligands (Cl, N, O). Similar chemical shifts to those of Pd3 were found for very small palladium nanoparticles on alumina [53] and iron oxide, [54] for [Pd(NH 3 ) 4 Cl 2 ] nanowires, [55] nitrogen-containing conjugated polymer-palladium systems, [56] and an amino-functionalized MCM-41-supported Pd2 complex [57] and are attributed to Pd 2 + bound to different ligands (Cl, N, O).…”
Section: Nature Of the Pd Species On Ncnts Determined By Xpssupporting
confidence: 59%
“…The Pd3 species is then assigned to divalent palladium. Similar chemical shifts to those of Pd3 were found for very small palladium nanoparticles on alumina [53] and iron oxide, [54] for [Pd(NH 3 ) 4 Cl 2 ] nanowires, [55] nitrogen-containing conjugated polymer-palladium systems, [56] and an amino-functionalized MCM-41-supported Pd2 complex [57] and are attributed to Pd 2 + bound to different ligands (Cl, N, O). Freund and co-workers studied the deposition of Pd on Fe 3 O 4 (111) from an alkaline solution of Pd 2 + and showed that polynuclear Pd n -hydroxo complexes were adsorbed on the carrier surface.…”
Section: Nature Of the Pd Species On Ncnts Determined By Xpssupporting
confidence: 59%